(untitled) (Perner’s Contacts, 2009)
Article is an insight to location and allocation analysis from optimization criteria view point and its usage. Dealt with reasons, why is worth to search another possible solutions of location problems. I suggest rate of return as optimization criteria, and so replenishing classic profit maximization or cost minimization. At the end I present an experimental results of comparison between rate of return and profit maximization.